Body armor for stab and spike protection, Part 1: Scientific literature review. Issue 7 (April 2018) - Nayak, Rajkishore; Crouch, Ian; Kanesalingam, Sinnappoo; Ding, Jie; Tan, Ping; Lee, Bin; Miao, Menghe; Ganga, Deepak; Wang, Lijing
Since the invention of small arms ammunition, the human torso has required protection from hand-gun bullets, and today's civil and military personnel are regularly clad in soft body armor systems to cope with these threats. However, increasingly, the threat spectrum has widened to include a plethora of both edged and pointed weapons. Over the past two decades in particular, this has required development of either specific soft armors to defeat that particular threat, or the development of multi-threat vests that can resist both hand-gun bullets and knife and spike attacks. In this review, we provide more details about the various material combinations that are used to defeat a knife or spike, since these armor materials are a lot different from the conventional aramid fabrics, and numerous, widely-different solutions are being pursued. The penetration mechanisms associated with the various forms of attack—stabbing and slashing—are discussed, as well as the use of new fibers, shear thickening fluids, and nano-materials in developing these body armor systems.